Prognostic and Therapeutic Utility of Variably Expressed Cell Surface Receptors in Osteosarcoma. (2nd February 2021) - Zvi, Yoav; Ugur, Elif; Batko, Brian; Gill, Jonathan; Roth, Michael; Gorlick, Richard; Hall, David; Tingling, Janet; Barkauskas, Donald A.; Zhang, Jinghang; Yang, Rui; Hoang, Bang H.; et al.
Abstract : Background . Six cell surface receptors, human epidermal growth factor receptor-2 (Her-2), platelet-derived growth factor receptor- β (PDGFR- β ), insulin-like growth factor-1 receptor (IGF-1R), insulin receptor (IR), c-Met, and vascular endothelial growth factor receptor-3 (VEGFR-3), previously demonstrated variable expression across varying patient-derived and standard osteosarcoma (OS) cell lines. The current study sought to validate previous expression patterns and evaluate whether these receptors offer prognostic and/or therapeutic value. Methods . Patient-derived OS cell lines ( n = 52) were labeled with antibodies to Her-2, PDGFR- β, IGF-1R, IR, c-Met, and VEGFR-3. Expression was characterized using flow cytometry. The difference in geometric mean fluorescent intensity (geoMFIdiff = geoMFIpositive − geoMFInegative ) was calculated for each receptor across all cell lines. Receptor expression was categorized as low (Q1), intermediate (Q2, Q3), or high (Q4). The event-free survival (EFS) and overall survival for the six cell surface receptors were estimated by the Kaplan–Meier method. Differences in hazard for EFS event and overall survival event for patients in each of the three expression levels in each of the six cell surface receptors were assessed using the log-rank test. Results . All 6 receptors were variably expressed in the majority of cell lines. IR and PDGFR- β expressions were found to be significant predictors for EFS amongst patients with nonmetastatic disease (p = 0.02 and 0.01, respectively). The hazard ratio for EFS was significantly higher between high IR and intermediate IR expression (HR = 2.66, p = 0.02 ), as well as between high PDGFR- β and intermediate PDGFR- β expression (HR = 5.68, p = 0.002 ). Her-2, c-Met, IGF-1R, and VEGFR-3 were not found to be significant predictors for either EFS or overall survival. Conclusion . The six cell surface receptors demonstrated variable expression across the majority of patient-derived OS cell lines tested. Limited prognostic value was offered by IR and PDGFR- β expression within nonmetastatic patients. The remaining receptors do not provide clear prognostic utility. Nevertheless, their consistent, albeit variable, surface expression across a large panel of patient-derived OS cell lines maintains their potential use as future therapeutic targets.